Recursos geradores de vantagem competitiva: o caso de um restaurante de praia no litoral leste cearense - Nunes, Ianca da Silva (Universidade Federal Rural do Semi-Árido, 2018)
Organizations are embedded in a complex and dynamic environment. Rapid changes in the organizational environment require managers to quickly make decisions against possible external threats that may arise, as well as take advantage of any opportunities that may arise. In this context, the use of strategies capable of conferring competitive advantages becomes essential for the survival of companies, making their internal resources characterized as central elements in the search for these advantages. Knowing this, present research using the single case study method, objective to evaluate the competitiveness of a beach restaurant located in the east coast of Ceará based on the theory of competitive advantage based on the resources of the firm. To achieve this goal, a qualitative research was carried out where interviews were conducted with semi structured script for data collection. The information collected was transcribed, arranged in categories and analyzed through content analysis. In this way, the present research identified that the restaurant has strategic resources that contribute to the strengthening of its competitiveness since it was verified in the enterprise the presence of resources that provide sustainable competitive advantage (physical structure, reputation and financial capital) and temporary competitive advantage (restaurant menu and planning, coordination and control systems). There are still three resources that provide competitive parity that are the services inputs, and the experiences knowledge and skills of the employees.
Monografia
Keywords: Vantagem competitiva; Visão baseada em Recursos; VRIO; Competitive Advantage; Resource Based View; VRIO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO